A forma do medo (1926) - Du Bois, W. E. B.; Monti (tradução), Isabela Vicente (Afro-Ásia, 2024)
Tradução de: W. E. B. Du Bois, “The Shape of Fear”, The North American Review, v. 223, n. 831 (1926), pp. 291-304.